PrBaCo2-xTaxO5+δ based composite materials as cathodes for proton-conducting solid oxide fuel cells with high CO2 resistance. (6th November 2020) - Wang, Di; Xia, Yunpeng; Lv, Huanlin; Miao, Lina; Bi, Lei; Liu, Wei
Abstract: PrBaCo2 O5+δ (PBC) with high catalytic activity is identified as a prospective cathode material for intermediate temperature solid oxide fuel cells (IT-SOFCs). However, its poor chemical stability hinders its application. To address this problem, a Ta-doping strategy was presented in this study. The cathode with Ta-doping PBC was applied in proton conducting SOFCs. And the influence of Ta-doping on the crystal structure, electrochemical performance, structure stability and electrical conductivity of PBC was investigated. The resistance to CO2 of PBC at elevated temperature is significantly improved with Ta-doping. The electrochemical performance measurements indicated that a low Ta-doping concentration did not change the performance of the cells obviously, while large Ta-doping concentration could lower the fuel cell performance. Highlights: Tantalum element was successfully doped into the crystal lattice of PBC. Ta-doped PBC was successfully applied in H–SOFC. The resistance to CO2 of PBC at elevated temperature is significantly improved with Ta-doping.